Moral Self-Identity in ESG Investment Decisions: Evidence from Generation Z Investors - Purnama, Beatrice Alexandra Puteri; Hastuti, Maria Eugenia; Purnomo, Hanny (Akuntansi dan Teknologi Informasi, 2026)
Purpose – This study aims to examine how Generation Z perceives Environmental, Social, and Governance (ESG) factors in the investment decision-making process and to explain how individuals' moral self-identity influences the use of sustainability-related information. Methods – We use a qualitative interpretive approach and semi-structured interviews with nine members of Investor Club X who possessed investment experience and varying levels of ESG understanding. The data were analyzed using thematic coding, supported by source, method, and theory triangulation to enhance the credibility of the findings. Findings - The findings indicate that ESG has not yet become the primary determinant of Generation Z’s investment decisions. Financial return, investment risk, and corporate growth prospects remain the dominant considerations, while ESG serves as a complementary factor, particularly for long-term investors. Moral self-identity shapes how investors interpret ESG information, with individuals who possess stronger moral self-identities demonstrating greater attention to sustainability reports than those adopting short-term investment strategies. Implications - This study contributes to the growing body of sustainability research by providing insights into Generation Z’s investment behavior and highlighting the role of moral values in ESG-oriented investment decision-making. Originality - This study integrates the perspective of Moral Self-Identity Theory to explain Generation Z’s investment decisions, an approach that remains relatively underexplored in ESG research within the Indonesian context.